Propriedades vibracionais e elétricas da Perovskita dupla ordenada Ba2BiSbO6 - Castro Junior, Manoel Carvalho (2008)
In this work were performed investigations about the vibrational and electric properties of the double ordered complex perovskite Ba2BiSbO6 , for diferent values of temperature, hydrostatic pressure and oscillating field frequency. The vibrational properties were investigated using Raman spectroscopy and the classical phonon calculation by FG Wilson method. The Raman spectra were acquired in the temperature range between 10 K and 573 K and at pressures up to 7.67 GPa. Both structural phase transition observed by Neutrons and X-ray difraction investigations were observed in the temperature dependent Raman spectra. The phase transition R3(S26)→Fm3m (O5h) was observed at around 515 K by the extinction of a mode of the rhombohedral phase localized at around 63 cm-1 and subtle changes in the temperature dependence of the wavenumbers and integrated area of the observed modes. The R3(S26)→I2/m(C52h) phase transition was observed between 250 and 260 K by the change in the intensities of the stretching and bending SbO7-6 octahedral modes. At 10 K was observed a new mode belonging to the monoclinic phase and assigned as Ag. The assignment of the modes in the rhombohedral, monoclinic and cubic phases was performed with basis on the classical phonons calculations by the FG Wilson method. Under hydrostatic pressure the R3(S26)→I2/m(C52h) phase transition was observed by the change in the slope of the temperature dependence of the wavenumbers of the observed modes. The electrical properties were obtained by impedance spectroscopy between room temperature and 560 K. The analysis of the frequency dependence of the imaginary part of the electrical modulus and impedance show that, at low temperatures, only a relaxation process due to the bulk is observed whose the relaxation frequency is thermally activated and follows an Arrhenius law behavior. When the temperature arises, a second relaxation process, whose relaxation frequency is also thermally activated, is observed due, probably, to the grain boundary. The phase transition R3(S26)→Fm3m (O5h) was not observed at high temperatures in the dielectric constant.